Hyperbaric Oxygen Therapy Can Induce Neuroplasticity and Significant Clinical Improvement in Patients Suffering From Fibromyalgia With a History of Childhood Sexual Abuse—Randomized Controlled Trial - Hadanny, Amir; Bechor, Yair; Catalogna, Merav; Daphna–Tekoah, Shir; Sigal, Tal; Cohenpour, Mehrzad; Lev-Wiesel, Rachel; Efrati, Shai (Frontiers in Psychology, 2018)
Background: Fibromyalgia syndrome (FMS), a condition considered to represent a prototype of central sensitization syndrome, can be induced by different triggers including childhood sexual abuse (CSA). Recent studies have demonstrated hyperbaric oxygen therapy (HBOT) can induce neuroplasticity and improve clinical outcome of FMS. The aim of the current study was to evaluate the effect of HBOT on patients suffering from FMS with a history of CSA. Materials and methods: A prospective randomized clinical trial conducted between July 2015 and November 2017 included women with a history of CSA who fulfilled fibromyalgia diagnosis criteria for at least 5 years prior to inclusion. Included participants (N = 30) were randomly assigned to treatment group, treated with 60 HBOT sessions and a control/crossover group received psychotherapy. After the control period, the control/crossover group was crossed to HBOT. Clinical outcomes were assessed using FMS questioners, post-traumatic stress disorder (PTSD) questioners and quality of life questioners. Objective outcome were assessed using brain function and structure imaging. Findings: Following HBOT, there was a significant improvement in all FMS questionnaires (widespread pain index, Fibromyalgia symptoms severity scale, Fibromyalgia functional impairment), most domains of quality of life, PTSD symptoms and psychological distress. The same significant improvements were demonstrated in the control following crossover to HBOT. Following HBOT, brain SPECT imaging demonstrated significant increase in brain activity in the prefrontal cortex, orbital frontal cortex, and subgenual area (p < 0.05). Brain microstructure improvement was seen by MRI-DTI in the anterior thalamic radiation (p = 0.0001), left Insula (p = 0.001), and the right Thalamus (p = 0.001). Conclusion: HBOT induced significant clinical improvement that correlates with improved brain functionality and brain microstructure in CSA related FMS patients. Trial Registration:www.Clinicaltrials.gov, identifier: NCT03376269. url: https://clinicaltrials.gov/show/NCT03376269